Cesar Chavez - Peña, Michael 1976-; Ferrera, America 1984-; Dawson, Rosario 1979-; Luna, Diego 1979-; Pearson, Keir (Pantelion, 2014)
The story of the famed civil rights leader and labor organizer torn between his duties as a husband and father and his commitment to securing a living wage for farm workers. Chavez embraced non-violence as he battled greed and prejudice in his struggle to bring dignity to people. He inspired millions of Americans who never worked on a farm to fight for social justice. His triumphant journey is a remarkable testament to the power of one individual's ability to change the world